Erianin induces triple-negative breast cancer cells apoptosis by activating PI3K/Akt pathway. Issue 6 (25th June 2021) - Xu, Yonggang; Fang, Rong; Shao, Jie; Cai, Zihao
Abstract: Background: Triple-negative breast cancer (TNBC) is a refractory subtype of breast cancer, 25–30% of which have dysregulation in the PI3K/AKT pathway. The present study investigated the anticancer effect of erianin on TNBC cell line and its underlying mechanism. Methods: After treatment with erianin, MTT assay was employed to determine the MDA-MB-231 and EFM-192A cell proliferation, the nucleus morphological changes were observed by DAPI staining. The cell cycle and apoptotic proportion were detected by flow cytometry. Western blot was performed to determine the cell cycle and apoptosis-related protein expression and PI3K pathways. Finally, the antiproliferative activity of erianin was further confirmed by adding or not adding PI3K agonists SC79. Results: Erianin inhibited the proliferation of MDA-MB-231 and EFM-192A cells in a dose-dependent manner, the IC50 were 70.96 and 78.58 nM, respectively. Erianin could cause cell cycle arrest at the G2 /M phase, and the expressions of p21 and p27 were up-regulated, while the expressions of CDK1 and Cyclin B1 were down-regulated. Erianin also induced apoptosis via the mitochondrial pathway, with the up-regulation of the expression of Cyto C, PARP, Bax, active form of Caspase-3, and Caspase-9. Furthermore, p-PI3K and p-Akt expression were down-regulated by erianin. After co-incubation with SC79, the cell inhibition rate of erianin was decreased, which further confirmed that the attenuated PI3K/Akt pathway was relevant to the pro-apoptotic effect of erianin. Conclusions: Erianin can inhibit the proliferation of TNBC cells and induce cell cycle arrest and apoptosis, which may ascribe to the abolish the activation of the PI3K/Akt pathway.